Assessment of the Saccular Function in Children with Spastic Cerebral Palsy - Akbarfahimi, N.; Hosseini, S.A.; Rassafiani, M.; Rezazadeh, N.; Ghomsheh F. Tabatabai; Shahshahani, S.; Karimlou, M. (Нейрофизиология, 2016)
Our investigation was designed to assess the saccular function of the vestibular system upon postural control dysfunction amongst children with spastic cerebral palsy (CP) using recording of cervical vestibular evoked myogenic potentials (cVEMPs), as well as to compare such findings with those in healthy subjects. Sixty two children (aged 7-12 years) were enrolled and assigned into two groups. There were 31 cases of spastic CP with the functional levels of I or II according to the Gross Motor Function Classification System in the patient group and 31 aged-matched healthy children as controls. The examined parameters were the latencies of the P₁₃ and N₂₃ waves, P₁₃–N₂₃ peak-to-peak amplitude, amplitude asymmetry ratio (AAR) and the cVEMP threshold. The cVEMP responses were recorded in 93.5 % of cases in the CP group and in all healthy subjects. Only 51.6% of the CP-group cases were within the normal AAR spectrum range. There were significant differences between the two groups with regard to the N₂₃ wave latency (P < 0.001), P₁₃–N₂₃ wave amplitude (P < 0.001) and cVEMP threshold (P<0.05). The significant difference in the cVEMP measured values between the CP cases and healthy controls may be attributed to a motor development delay and deficits in the vestibulo-collic reflex pathway. Our findings suggest that cVEMP recording may be considered an auxiliary tool for the assessment of the vestibular system in children with spastic CP. Such a test is expected to help more adequate planning for interventions.